The Growth of Small Firms: An Alternative Look Through The Lens of Effectuation - Afolayan, Oluwaseun Babatope (Université d'Ottawa / University of Ottawa, 2014)
The importance of small firms in a country’s development cannot be over-emphasized. In particular, it is important for them to grow in order to sustain their contributions to a country’s economy. Studies have shown how firms achieve growth using the traditional model of decision making (causation) in which planning, market research and forecasting are used to gain relevant information about the firm’s market/industry. This planning enables the firms to compete favourably with other existing firms in the market. Effectuation as an alternative theory involves decision-making processes under conditions of uncertainty where there is no adequate knowledge of the market due to its latent and emerging nature. Effectuation has been used to examine various concepts in entrepreneurship, but there has been no real effort to apply it to the growth of small knowledge-intensive firms (SKIFs). This study, based on in-depth interviews with six SKIFs, highlights how effectuation can be applied to the growth of SKIFs and it examines how the four underlying principles of contingencies, affordable loss, strategic relationships and adaptation contribute to SKIF growth. In addition, elements of causation are also shown to be relevant, leading to the conclusion that the two models can be used jointly to achieve growth of SKIFs.
Keywords: Effectuation; Growth; Small firm growth; Small firms